2011
DOI: 10.1007/s00210-011-0696-9
|View full text |Cite
|
Sign up to set email alerts
|

Choreographing the adenylyl cyclase signalosome: sorting out the partners and the steps

Abstract: Adenylyl cyclases are a ubiquitous family of enzymes and are critical regulators of metabolic and cardiovascular function. Multiple isoforms of the enzyme are expressed in a range of tissues. However, for many processes, the adenylyl cyclase isoforms have been thought of as essentially interchangeable, with their impact more dependent on their common actions to increase intracellular cyclic adenosine monophosphate content regardless of the isoform involved. It has long been appreciated that each subfamily of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
35
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 67 publications
4
35
1
Order By: Relevance
“…The ADCY2 gene on chromosome 5p15.31 is expressed in the brain and encodes a cell membrane-bound enzyme for the synthesis of the second-messenger molecule cAMP. The ADCY2 protein is primarily regulated by heterotrimeric G proteins and produces cAMP in response to extracellular hormones and neurotransmitters that bind as ligands to G protein-coupled receptors (GPCRs) 23 . ADCY2 is also regulated by the protein kinase C (PKC) and the RAF kinase.…”
Section: Discussionmentioning
confidence: 99%
“…The ADCY2 gene on chromosome 5p15.31 is expressed in the brain and encodes a cell membrane-bound enzyme for the synthesis of the second-messenger molecule cAMP. The ADCY2 protein is primarily regulated by heterotrimeric G proteins and produces cAMP in response to extracellular hormones and neurotransmitters that bind as ligands to G protein-coupled receptors (GPCRs) 23 . ADCY2 is also regulated by the protein kinase C (PKC) and the RAF kinase.…”
Section: Discussionmentioning
confidence: 99%
“…They can bind to AC to regulate cAMP synthesis and sequester phosphodiesterases to break down this second messenger locally. In addition, they tether PKA to specific subcellular sites, thereby focusing the activity of PKA toward relevant substrates (7,52). In vascular SMCs, studies have shown that the AKAP complex regulates specific vascular SMC functions, such as inhibition of cell migration, by causing localized changes in actin dynamics and reduction in cell proliferation and neointimal hyperplasia by stimulating cAMP-induced transcription and increasing the levels of the cyclin-dependent kinase-2 inhibitor p27kip1 (30,59).…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Figure 12, when activated by ligandreceptor interaction, Gα s activates the closely associated adenylyl cyclase (AC), an enzyme that rapidly catalyzes the formation of cyclic AMP (cAMP) from ATP. Within the AC family of proteins, nine isoforms have been identified, and the effects of those isoforms are dependent on "signalosomes" recruited by each specific isoform 130 . As studied in the rat nephron, AC isoforms II, III, VI, VII, and IX are expressed in the proximal tubule, with II, III, and IX confirmed through IHC to be expressed only in the apical membrane (IHC data unavailable for VI and VII) 131 .…”
Section: Pth-induced Pka Signalingmentioning
confidence: 99%